Assessment of Microsurgery Simulation Course Access in Plastic Surgery Training Programs - Elver, Ashlie A.; Egan, Katie G.; Phillips, Brett T. (Journal of Reconstructive Microsurgery, 2024)
Background Microsurgery requires complex skill development with a steep learning curve for plastic surgery trainees. Flap dissection courses and simulation exercises are useful to acquire these skills. This study aims to assess plastic surgery training programs' access to and interest in microsurgical courses.Methods A survey was distributed to plastic surgery residency and microsurgery fellowship program directors (PDs). The survey collected program demographics and attendance of trainees at structured microsurgical skills or flap dissection courses. We assessed if PDs thought trainees would benefit from instructional courses.Results There were 44 residency PD responses (44/105, 41.9%, 36 integrated, 8 independent), and 16 fellowship PD responses (16/42, 38.1%). For residency PDs, 54.5% (24/44) sent residents to flap courses, and 95% (19/20) of remaining PDs felt residents would benefit from attending. In addition, 59.1% of programs (26/44) sent residents to microsurgical skills courses, and 83.3% (15/18) of remaining PDs felt residents would benefit from attending. When examining fellowship PDs, 31.2% of programs (5/16) sent fellows to flap dissection courses and 10/11 of remaining PDs felt fellows would benefit from attending a course (90.1%). Half of programs (8/16) sent fellows to microsurgical skills courses, and 7/8 remaining PDs felt fellows would benefit from attending (87.5%).Conclusion Only half of the plastic surgery trainees have access to microsurgical skills and flap dissection courses. The majority of residency and fellowship PDs feel that training courses are valuable. Expanding access to these courses could provide a significant benefit to microsurgical education in plastic surgery training.
Keywords: resident education; surgical education; simulation; microsurgery